ANALISA PENGGUNAAN LENSA SILINDER UNTUK MENGUBAH BENTUK BERKAS LASER DIODA MENJADI BENTUK GARIS - Muhammad Mashuri; Minarni '; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research on the application of cylindrical lenses to change beam shape of diode lasers from  eliptical to line shape has been conducted.  The beam characteristic of the lasers before and after using the lenses were analyzed by a calibrated photodiode and a CCD camera. The distance between CCD camera and the lenses were also varied to obtain the optimal length of the line.  The diode lasers used were  λ=830 nm Coherent diode laser with beam size 0,6 mm and 0,9 mm in x and y axis and  λ=638 nm Aixiz diode laser with beam size 1,2 mm and 1,6 mm in x and y axis were used.  Three  cylindrical lenses with three  different focal length were used whice were 50 mm, 75 mm, and 95 mm respectively.  The results showed that the maximum line lengths (L) of  λ=830 nm diode laser were 1,86 mm, 2,55 mm, and 1,39 mm respectively. For the  λ=638 nm diode laser the maximum line length (L) were 3,74 mm, 4,32 mm, and 3,87  mm respectively to the same focal length. The result also showed that the bigger λ produced the shorter line (L) than the smaller λ. For the biggest focus need the longest distance (z) to produce the longest line.